Role of Innate Lymphocytes in Infection and Inflammation - Koyasu, Shigeo; Moro, Kazuyo (Frontiers in Immunology, 2012)
Cooperation of innate and adaptive immune responses is critical for the protective immunity against various invading microbes. Distinct types of effector T cells play different roles in adaptive immune responses. Th1 cells play important role in the control of intracellular bacteria by producing IFN-γ to activate macrophages. Th1 cells are also important in anti-viral immunity by producing IFN-γ and activating cytotoxic T lymphocytes. Th2 cell-derived cytokines are important in activating mast cells, eosinophils and goblet cells in anti-helminth immunity. Th17 cells are pivotal for the inflammatory response mediated by neutrophils to fight against extracellular bacterial infection. In all cases, it is critical to limit the growth and expansion of invading microbes by innate immune responses until antigen-specific adaptive immune responses are established. Recent studies have identified multiple subsets in innate lymphocyte corresponding to Th subsets. cNK cells, RORγ+ LTi-related cells and Th2-type innate lymphocytes play distinct roles in innate immune responses by producing Th1, Th17 and Th2 cytokines, respectively. Cooperation between those innate lymphocytes and antigen-specific T and B cells are likely important in protective immunity against distinct types of microbes. Most recently identified subset is RORγ-independent Lin-Thy-1+IL-7R+GATA3+　innate lymphocyte subset, which is Id2- and IL-7-dependent. This population is capable of producing Th2 cytokines, most notably IL-5 and IL-13, and plays a major role in the innate immune responses during anti-helminth immunity. In addition, these cells are likely involved in pathophysiology of some types of allergic diseases. We summarize here current knowledge about various innate lymphocyte subsets. In particular, we focus on the Th2-type innate lymphocyte subset.